Assessing knowledge, attitude, practice, and preparedness of hospital pharmacists in Lebanon towards COVID-19 pandemic - Zeenny, Rony M. (2020)
Background During the COVID-19 pandemic, the Lebanese government has taken the proactive anticipatory measure to minimize the infection rates. Despite the pivotal role of the pharmacists working in hospital settings, hospital pharmacists have not been engaged in the emergency preparedness for hospitals. The primary objective of this survey is to assess the knowledge, attitude, and practice of hospital pharmacists in Lebanon towards COVID-19 pandemic and explore the level of health emergency preparedness of Lebanese hospitals in response to this outbreak. Methods A standardized English-based, anonymous and online questionnaire was diffused via social media platforms to all Lebanese hospital pharmacists. The questionnaire consisted of 78 questions related to sociodemographic characteristics, knowledge-based, attitude-based, practice questions, and pandemic preparedness. Descriptive statistical analysis was used to summarize data. Results A total of 81 questionnaires were completed; the participants were able to know > 90% of the knowledge-based questions regarding COVID-19. Most of the respondents were concerned about getting infected and their families due to their professional exposure. Similarly, around 67% were following the safety recommendations. Most of the participants agreed that they are facing shortages, rising prices, and delays in supply of masks and sanitizers. In terms of COVID-19 readiness, about 50% of hospitals have taken practical steps. Conclusions Our findings revealed an appropriate level of knowledge and good practice towards COVID-19, among the respondents from Lebanese hospitals. National organizations may benefit in utilizing the expertise of the hospital pharmacists to be able to minimize/avoid future waves of COVID-19 if it emerges.